The Essential Questions : interview your family to uncover stories and bridge generations - Keating, Elizabeth Lillian ([New York] : TarcherPerigee, an imprint of Penguin Random House LLC, 2022)
"Just as the oral histories of people around the world are disappearing amid rapid change, there is a risk that your family's personal stories, too, will be lost forever. In The Essential Questions, anthropologist Elizabeth Keating helps you to uncover the unique memories of your parents and grandparents and to create lasting connection with them in the process"--.
Introduction: The anthropology of family -- Tips on interviewing your family -- Questions to get some basic background -- Questions on space : learning about where your elders grew up -- Questions on time : connecting with the history of your family -- Questions on social interactions : the importance of everyday encounters -- Questions on becoming : rites of passage and how your elders were raised -- Questions on identity : the factors that made you who you are -- Questions on the body and adornment : an expression of how you see yourself and others -- Questions on belief : the ideas that shaped you and your family -- Questions on kinship and marriage : the making of a family -- Questions on material culture : your family's most treasured possessions -- Questions on fear : learning courage through fear -- Questions on memory : the things you'll never forget -- What do you wish people knew about you? -- Conclusion: How to avoid genealogical amnesia.
"A TarcherPerigee Book."
new book 2024 winter.
Includes bibliographical references.
Keywords: Interviewing in genealogy -- Popular works; Oral history -- Popular works; Families -- History